Politics Unusual? Facebook and Political Campaigning during the 2013 Harmonised Elections in Zimbabwe. Issue 1 (2nd January 2018) - Mare, Admire
ABSTRACT: Single media reductionism has dominated research which examines the relationship between digital technologies and political processes in most mature democracies. This kind of research has also tended to overhype the role of new media platforms in influencing electoral processes, thereby obfuscating the complex and sometimes unpredictable intermingling between media (both old and new forms) and contextual factors, especially in transitional societies. Using data gathered through a combination of virtual ethnography and qualitative content analysis, the study investigates how three major political parties and candidates in Zimbabwe used Facebook for campaign purposes during the so-called "watershed" 2013 elections. The results suggest that political parties and candidates appropriated Facebook to organise internal and external activities. The study also shows that although new media has partly "digitised" the Zimbabwean electoral processes and contacting practices between politicians and citizens with access to the social and mobile media internet, it has also ambivalently created communication hierarchies and participation inequalities between the connected (mostly urbanites) and disconnected (especially rural) voters. It also demonstrates that rather than promoting "transparency" politicians' visibility on Facebook engenders a new calibre of "celebrity"—politicians who are transiently accessible online yet very much inaccessible offline.